(untitled) (Revista Brasileira de Plantas Medicinais, 2024)
The present study aimed to identify the primary plant species used for treating livestock in the Lower-Mid São Francisco River region of Northeast Brazil. Conducted in rural areas of the state of Bahia, this study focused on traditional shared-pasture farming communities. Interviews with 42 livestock farmers were conducted to evaluate the medicinal use of plants in treating livestock diseases. The use value, citation frequency, relative citation frequency, frequency index, cultural importance index, and relative importance of plant species were calculated. A total of 45 plant species were cited, belonging to 19 families and 38 genera. Mimosa tenuiflora (Willd.) Poir. was the most cited species and had the highest relative importance value (0.750). Spondias tuberosa Arruda had the highest number of use reports (8) and frequency index (19). The stem was the most used part of the plant, followed by the leaves. This study demonstrated that the use of medicinal plants remains common in several communities in the semiarid region of Northeast Brazil, with plants serving diverse medicinal purposes and preparations in shared-pasture livestock farming.